Optimalisasi Penerapan MLC (Maritime Labour Convention) di Atas Kapal KM Bukit Siguntang - Dwi Anggraeni Wulandari; Indah Ayu Johanda Putri; Muhamad Imam Firdaus; Muhammad Nadjib Lawangi; Arleiny Arleiny (Dinamika Bahari, 2021)
Indonesia is an archipelagic country with 17,508 islands. Therefore, transportation by sea is very much needed to support trade flows in reaching areas between islands with one another through national and international waters. The purpose of this study was to determine the optimization of the implementation of the MLC (Maritime Labor Convention) on ships and to determine the effect of the implementation of the MLC (Maritime Labor Convention) for the welfare of seafarers. The data collection method is survey and interview methods. This research is included in qualitative research. The results of this study indicate that the 2006 MLC regarding the welfare of seafarers onboard KM Bukit Siguntang has been implemented well, but the rest time is not optimal so it is necessary to pay attention to its optimization. The implementation of the 2006 MLC had a major impact on the welfare of seafarers on board.